Understanding intellectual disability through RASopathies - San Martín, Alvaro (2014)
Intellectual disability, commonly known as mental retardation in the International Classification of Disease from World Health Organization, is the term that describes an intellectual and adaptive cognitive disability that begins in early life during the developmental period. Currently the term intellectual disability is the preferred one. Although our understanding of the physiological basis of learning and learning disability is poor, a general idea is that such condition is quite permanent. However, investigations in animal models suggest that learning disability can be functional in nature and as such reversible through pharmacology or appropriate learning paradigms. A fraction of the cases of intellectual disability is caused by point mutations or deletions in genes that encode for proteins of the RAS/MAP kinase signaling pathway known as RASopathies. Here we examined the current understanding of the molecular mechanisms involved in this group of genetic disorders focusing in studies which provide evidence that intellectual disability is potentially treatable and curable. The evidence presented supports the idea that with the appropriate understanding of the molecular mechanisms involved, intellectual disability could be treated pharmacologically and perhaps through specific mechanistic-based teaching strategies.